Nano mesoporous Ir / TiO2 crystal as well as preparation method and application thereof

By uniformly loading nano Ir particles on the surface of TiO2, nanomesoporous Ir/TiO2 crystals are formed, the problem of photocatalysts being easily corroded in high-salt seawater environments is solved, efficient photocatalytic hydrogen production performance is achieved, and the corrosion resistance and stability of the catalyst are significantly improved.

CN119733503APending Publication Date: 2025-04-01YUNNAN NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510012640.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing photocatalysts are prone to corrosion in high-salt seawater environments, resulting in catalyst deactivation and reducing their photocatalytic activity, limiting the commercial development of photocatalytic seawater hydrogen production technology.

Method used

Nanoscale Ir metal particles are loaded on the surface of TiO2 to form nanomesoporous Ir/TiO2 crystals, which have a mesoporous structure, a large specific surface area and a highly active crystal plane. Through the introduction of local plasma resonance effects and oxygen vacancies, the light absorption range is expanded and the photocatalytic performance is improved.

Benefits of technology

The corrosion resistance of the photocatalyst and the efficiency of photocatalytic hydrogen production in seawater are significantly improved, and the performance is better than that of traditional catalysts in simulated seawater environments, and the stability performance is maintained during the cycle reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119733503A_ABST
    Figure CN119733503A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photocatalysis, and particularly relates to a nano mesoporous Ir / TiO2 crystal as well as a preparation method and application thereof. According to the preparation method, a precursor Ir / K2Ti8O17 is prepared through a hot solvent method firstly, then formic acid is utilized to etch the precursor to form a nano mesoporous Ir / TiO2 crystal, Ir nano particles are evenly distributed, the size is 1-3 nm, and the surface of the crystal has rich (101) high-activity crystal faces and oxygen vacancy defects. According to the crystal, the light absorption range is remarkably enhanced to the near-infrared region through the local plasma resonance effect, and meanwhile, the mesoporous structure provides a large specific surface area and excellent reactant diffusivity. Compared with a traditional TiO2 catalyst, the nano mesoporous Ir / TiO2 crystal disclosed by the invention shows excellent corrosion resistance and efficient photocatalytic activity in photocatalytic seawater hydrogen production. The method is simple, convenient and efficient, the Ir metal utilization rate is high, the problems that precious metal is poor in dispersity, prone to agglomeration and the like are solved, and the method can be widely applied to the field of photocatalytic hydrogen production and has great significance in promoting green energy technology development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysis, and specifically relates to a nano-mesoporous Ir / TiO2 crystal, a preparation method and application thereof. Background Art

[0002] Green hydrogen is an efficient and clean energy carrier that can replace fossil fuels due to its high calorific value and pollution-free characteristics. It can effectively reduce carbon emissions and achieve the goal of carbon neutrality. Photocatalytic hydrogen production from seawater is considered to be a renewable technology for producing green hydrogen. The energy source for photocatalytic hydrogen production from seawater is widespread solar energy, and the raw material is the abundant seawater resources on the earth. Therefore, this technology is a low-cost, pollution-free and easy-to-operate hydrogen production technology. However, the high-salt environment in seawater usually corrodes the catalyst and causes unnecessary side reactions, resulting in catalyst deactivation and reducing its photocatalytic activity, which seriously inhibits its large-scale commercial development. Therefore, it is particularly important to develop a corrosion-resistant, high-performance photocatalyst.

[0003] Generally speaking, the main factors affecting the performance of photocatalytic hydrogen production from seawater are: 1) the photon utilization rate and carrier recombination rate of the catalyst; 2) the stability and corrosion resistance of the catalyst in a high-salt environment; 3) the specific surface area and active sites of the catalyst. A large specific surface area is conducive to the adsorption of reactants, and abundant reactive active sites are more conducive to the photocatalytic reaction; 4) Cl - and OH - The competitive adsorption reaction will produce unnecessary by-products Cl2 and ClO - , causing pollution to the environment.

[0004] Titanium dioxide (TiO2) is a commonly used photocatalyst with the characteristics of low price, stable thermochemical properties, strong redox ability and environmental friendliness. It is widely used in various fields of photocatalysis, such as photocatalytic hydrogen production from seawater, photocatalytic degradation of pollutants and heavy metal reduction. However, its wide band gap (3.2 eV) can only absorb ultraviolet light, but has a low response to visible light. In addition, the high recombination rate of photogenerated carriers restricts its wide application in the field of photocatalysis.

[0005] In order to solve the problems of low response of TiO2 to visible light and rapid carrier recombination, TiO2 is modified by ion doping, precious metal loading, photosensitization and semiconductor recombination based on the existing technology.

[0006] Among them, precious metal loading is a common means to improve photocatalytic performance. Precious metals loaded on TiO2 can act as co-catalysts to reduce the activation energy of the reaction on the one hand, and promote the separation of photogenerated carriers on the other hand. In addition, the interface between precious metals and TiO2 will also produce a local plasma resonance effect (LSPR), which enhances the light absorption efficiency, and near-field enhancement promotes the separation of photogenerated carriers; in addition, the photothermal effect will also increase the local temperature of the TiO2 surface, accelerate the transmission and redox ability of carriers, and thus improve the photocatalytic performance of TiO2-based photocatalysts.

[0007] In recent years, researchers have used a variety of titanium dioxide-based material systems for photocatalytic hydrogen production from seawater, such as P / Ni@TiO2, Cu2O / TiO2, b-TiO2, V Ti -TiO2 and Co@RuO x / TiO2, etc. Although the above materials have effectively improved the photon utilization rate and reduced the carrier recombination rate, they still face the problem of low photocatalytic efficiency and easy corrosion of catalysts, resulting in their photocatalytic performance in seawater being lower than that in pure water. At present, most of the co-catalysts used in photocatalytic hydrogen production from seawater are precious metal Pt, which has a low hydrogen evolution overpotential and activation energy, but the high price and corrosion resistance still need to be solved. Summary of the invention

[0008] To solve the above problems, on the one hand, the present invention provides a nano-mesoporous Ir / TiO2 crystal, which is composed of nano-scale Ir metal particles uniformly loaded on the TiO2 surface, wherein the Ir metal particle size is 1-3nm, the crystal surface has a mesoporous structure, and the exposed crystal plane is the (101) crystal plane.

[0009] Furthermore, the crystal has a specific surface area greater than 90 m 2 / g.

[0010] The (101) highly active crystal face exposed on the surface of the crystal of the present invention can effectively promote the separation of photogenerated electrons and holes, and the negative charge layer formed on the surface can prevent the adsorption of Cl⁻ ions in seawater and reduce the occurrence of side reactions; secondly, the uniform distribution of Ir nanoparticles and the size of 1-3 nm provide abundant active sites, and at the same time, the light absorption range of the photocatalyst is extended to the near-infrared region through the localized plasma resonance effect, which greatly improves the utilization efficiency of sunlight; in addition, the mesoporous structure also provides a large specific surface area and a good reactant diffusion channel, which helps to improve the catalytic efficiency; finally, the introduction of oxygen vacancy defects not only increases the light absorption capacity of the catalyst, but also reduces the recombination probability of photogenerated carriers, thereby further improving the photocatalytic performance. Taking the above factors into consideration, the crystal of the present invention exhibits excellent corrosion resistance and efficient photocatalytic seawater hydrogen production capacity, and performs better than traditional catalysts in a simulated seawater environment.

[0011] In another aspect, the present invention provides a method for preparing nano-mesoporous Ir / TiO2 crystals, comprising the following steps: Step 1: Dissolve Ti(C4H9O)4 and IrCl4·xH2O in ethylene glycol, add KOH solution, stir evenly and transfer to a stainless steel reactor. After constant temperature reaction, freeze centrifuge the product, wash it repeatedly, and dry it in a vacuum drying oven to obtain the precursor Ir / K2Ti8O 17 ; Step 2: Precursor Ir / K2Ti8O 17 Mix with HCOOH, after etching reaction, take the suspension, freeze centrifuge to obtain precipitation, wash repeatedly, and place the product in a vacuum drying oven to obtain nano-mesoporous Ir / TiO2 crystals.

[0012] The method for preparing nano-mesoporous Ir / TiO2 crystals of the present invention mainly comprises the following steps: using the precursor Ir / K2Ti8O 17 The Ti-O and KO bonds have different properties. The Ti-O bond is a covalent bond and is relatively stable, while the KO bond is an ionic bond and is relatively active. + Easy to be H + Ion etching precipitation. The precursor Ir / K2Ti8O 17 K in the channel + The [TiO6] octahedrons are expanded to form monodisperse Ir / TiO2 nanoparticles. Under strong hydrothermal conditions, these monodisperse Ir / TiO2 are highly aggregated through a directional attachment mechanism to form nano-mesoporous Ir / TiO2 crystals with consistent crystal orientation.

[0013] Furthermore, in step 1, the temperature in the reactor is controlled at 200° C. for 20 hours.

[0014] Furthermore, in step 2, the etching reaction is carried out in a closed stainless steel reactor.

[0015] Furthermore, in step 2, the etching reaction time is 2 hours.

[0016] Furthermore, in step 2, the centrifugation operation is performed under refrigerated conditions at 4° C. and a rotation speed of 8000 rpm.

[0017] Furthermore, in step 2, the temperature of the vacuum drying oven is 70°C.

[0018] In another aspect, the present invention provides an application of nano-mesoporous Ir / TiO2 crystals in photocatalytic hydrogen production from seawater, wherein the crystals are catalysts.

[0019] Furthermore, the photocatalytic performance of the crystal in a simulated seawater environment with a salt content of 3.5% is better than that in a pure water environment.

[0020] Beneficial effects of the present invention: (1) The nano-mesoporous Ir / TiO2 crystals prepared by the two-step etching method of the present invention have more pores, larger specific surface area and good crystallinity, which are conducive to the diffusion of reactants, provide more reactive sites and reduce the grain boundaries that serve as recombination centers; the exposed crystal face of the crystal is the (101) crystal face, which has high photochemical reaction activity, and the photogenerated electrons will preferentially migrate to the (101) crystal face to accelerate the catalytic reaction. In addition, the photogenerated electrons accumulated on the (101) crystal face will form a negative charge layer on the surface of Ir / TiO2, blocking the Cl in seawater. - Adsorbed to the catalyst surface, competitive reaction occurs, which can effectively avoid Cl - Corrosion catalyst, and improve the efficiency of photocatalytic seawater hydrogen production; Ir metal exists in the form of nanocrystals with uniform size distribution of 1-3nm and regular geometric morphology. The nanosize has a quantum size effect, which effectively improves the redox ability of the catalyst; in addition, Ir nanocrystals have good dispersion and no obvious agglomeration, which effectively increases the utilization rate of precious metal Ir, thereby improving the photocatalytic performance of the catalyst.

[0021] (2) The nano-mesoporous Ir / TiO2 crystals prepared by the two-step etching method of the present invention are rich in oxygen vacancy defects, which can introduce defect energy levels below the catalyst conduction band and broaden the light absorption range of the catalyst. In addition, more oxygen vacancy defects are conducive to the adsorption of reactants by the catalyst, which can effectively improve the photocatalytic performance of the catalyst. The crystals have obvious localized plasma resonance effect, which expands the light absorption range of the nano-mesoporous Ir / TiO2 crystals to the near-infrared region, and the heat generated by the photothermal effect accelerates the oxidation reaction, effectively improving the photocatalytic performance of the catalyst. In addition, the crystals have good corrosion resistance, and the photocatalytic hydrogen production performance in simulated seawater is better than that in pure water. After 10 cycles of reaction, there is no obvious decline in the catalyst performance.

[0022] (3) The nano-mesoporous Ir / TiO2 crystals prepared by the two-step etching method of the present invention have an Ir metal content of 0.76wt.%, and their photocatalytic hydrogen production performance from seawater is better than the performance of TiO2-based materials with Pt metal as a co-catalyst and a Pt content of 1 wt.% to 3wt.% reported in the literature, which greatly improves the utilization rate of Ir metal and reduces costs. In addition, during the preparation process, the freezing mode is used when separating the samples by high-speed centrifugation, which can effectively avoid the sample agglomeration caused by the heat generated during high-speed rotation, resulting in the performance degradation of the nano-mesoporous Ir / TiO2 crystals.

[0023] Based on the above beneficial effects, the present invention has good application prospects in the field of photocatalytic technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is a nitrogen isothermal adsorption-desorption curve diagram of the nano-mesoporous 1% Ir / TiO2 crystal in Example 1 of the present invention.

[0025] Figure 2 This is a transmission electron microscope image of the nano-mesoporous 1% Ir / TiO2 crystal in Example 1 of the present invention. The inset in the upper left corner is the fast Fourier transform (FFT).

[0026] Figure 3 This is a spherical aberration transmission electron microscopy image of the nano-mesoporous 1% Ir / TiO2 crystal in Example 1 of the present invention.

[0027] Figure 4 This is the UV-visible-near-infrared diffuse reflectance spectrum of the nano-mesoporous 1% Ir / TiO2 crystal in Example 1 of the present invention.

[0028] Figure 5 Graph showing the photocatalytic hydrogen production efficiency of the nano-mesoporous 1% Ir / TiO2 crystals in Example 1 of the present invention in simulated seawater and pure water, respectively.

[0029] Figure 6 This is a cyclic stability diagram of the photocatalytic hydrogen production from seawater using nano-mesoporous 1% Ir / TiO2 crystals in Example 1 of the present invention.

[0030] Figure 7 This is a diagram showing the efficiency of photocatalytic seawater hydrogen production from nano-mesoporous 1% Ir / TiO2 crystals and nano-mesoporous 5% Ir / TiO2 crystals in Example 1 and Implementation Example 2 of the present invention. DETAILED DESCRIPTION

[0031] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below with reference to the accompanying drawings and examples.

[0032] Example 1 The present invention provides a method for preparing nano-mesoporous Ir / TiO2 crystals, and the specific steps are as follows: Step 1: Dissolve 1 ml of Ti(C4H9O)4 and 10.2 mg of IrCl4·xH2O in 20 ml of ethylene glycol. After complete dissolution, slowly drip 20 ml of 3.56 mol / L KOH solution into the above solution to obtain a transparent and clear solution A. Then, magnetically stir solution A at 500 rpm for 2 hours. After stirring, transfer solution A to a 100 ml stainless steel reactor and react at 200°C in an oven for 20 hours. After the reaction is completed, freeze centrifuge the product at 8000 rpm and 4°C for 10 minutes, and wash it repeatedly with deionized water and anhydrous ethanol for 3 times. Finally, dry the cleaned product in a vacuum oven at 70°C overnight to obtain the precursor Ir / K2Ti8O 17 .

[0033] Step 2: 0.40 g of precursor Ir / K2Ti8O 17 It was mixed with 20 ml of HCOOH and then transferred to a 50 ml stainless steel reactor. The reaction was etched in an oven at 160°C for 2 hours. After the reaction, the suspension in the reactor was taken out and centrifuged at 8000 rpm and 4°C for 10 minutes. The suspension was washed three times with deionized water and anhydrous ethanol. Finally, the cleaned product was dried in a vacuum drying oven at 70°C overnight to obtain the target product, nano-mesoporous Ir / TiO2 crystals, recorded as 1% Ir / TiO2.

[0034] Figure 1 The nitrogen isothermal adsorption-desorption curve of the nano-mesoporous 1% Ir / TiO2 crystal in Example 1 of the present invention shows that the isotherm type is type IV and there is no obvious adsorption platform, indicating that the nano-mesoporous 1% TiO2 crystal has an irregular slit mesoporous structure and a specific surface area of ​​90.98 m 2 / g.

[0035] Figure 2 This is a transmission electron microscope image of the nano-mesoporous 1% Ir / TiO2 crystal in Example 1 of the present invention. The inset in the upper left corner is a fast Fourier transform image. It can be seen that it has good crystallinity and the crystal plane orientation is (101) crystal plane.

[0036] Figure 3 This is a spherical aberration transmission electron microscopy image of the nano-mesoporous 1% Ir / TiO2 crystal in Example 1 of the present invention. It can be seen that the crystal is composed of nano-scale Ir metal particles uniformly loaded on the TiO2 surface, wherein the Ir metal particle size is 1-3nm, and the crystal surface has a mesoporous structure; among them, the Ir nanocrystals have good dispersion, no obvious agglomeration phenomenon, and regular geometric morphology.

[0037] Figure 4This is the UV-Vis-NIR diffuse reflectance spectrum of the nano-mesoporous 1% Ir / TiO2 crystal in Example 1 of the present invention. It can be seen that the light absorption range of the nano-mesoporous 1% Ir / TiO2 crystal extends to the near-infrared region, which is due to the synergistic effect of the LSPR effect and oxygen vacancy defects.

[0038] Figure 5 The photocatalytic hydrogen production efficiency diagram of the nano-mesoporous 1% Ir / TiO2 crystals in Example 1 of the present invention in simulated seawater and pure water respectively. It can be seen that the hydrogen production performance of the nano-mesoporous 1% Ir / TiO2 crystals in simulated seawater with a salt content of 3.5% is better than that in pure water, indicating that it has good corrosion resistance.

[0039] Figure 6 This is a cyclic stability diagram of the photocatalytic hydrogen production from seawater by the nano-mesoporous 1% Ir / TiO2 crystals in Example 1 of the present invention. It can be seen that after 10 cycles of reaction, the photocatalytic hydrogen production performance of the nano-mesoporous 1% Ir / TiO2 crystals has no obvious decrease, indicating that it has good stability.

[0040] Example 2 The present invention provides a method for preparing nano-mesoporous Ir / TiO2 crystals, the only difference being that in step 1, IrCl4·xH2O is 50.8 mg, and finally the target product, nano-mesoporous Ir / TiO2 crystals, are obtained, which are recorded as 5% Ir / TiO2.

[0041] Figure 7 The photocatalytic hydrogen production efficiency diagram of the nano-mesoporous 1% Ir / TiO2 crystal and the nano-mesoporous 5% Ir / TiO2 crystal in Example 1 and Example 2 of the present invention shows that the hydrogen production performance of the nano-mesoporous Ir / TiO2 crystal obtained in the two different examples is significantly higher than that of pure TiO2. This is because the Ir nanocrystals can effectively reduce the activation energy of the reaction after loading, which is beneficial to improving the photocatalytic performance of TiO2. The photocatalytic performance of the nano-mesoporous 1% Ir / TiO2 crystal prepared in Example 1 is significantly better than that of the nano-mesoporous 5% Ir / TiO2 crystal prepared in Example 2, which is due to the addition of less IrCl4·xH2O in Example 1, which effectively prevents the clustering of Ir nanocrystals and maximizes the use of Ir nanocrystals, thereby significantly improving the photocatalytic hydrogen production performance of seawater.

[0042] Preferably, when Ti(C4H9O)4 and IrCl4·xH2O are dissolved in ethylene glycol, ultrasonic wave is used to assist mixing, so as to enhance the uniform dispersion of reactants, reduce local concentration differences, and improve the uniformity of precursor formation; during the hydrothermal reaction, ultrasonic wave treatment is intermittently applied to the reactor to prevent excessive aggregation of crystals through cavitation effect, thereby promoting the formation of Ir particles in K2Ti8O 17Evenly distributed nanocrystals are formed on the surface; in the reaction process of etching the precursor with HCOOH, ultrasonic-assisted treatment is combined to promote the uniformity of the etching process, accelerate the removal of K⁺ ions, optimize the pore structure of TiO2, and further increase the specific surface area. That is, by introducing ultrasonic-assisted technology in the preparation process of nano-mesoporous Ir / TiO2 crystals, the morphology of the crystals is optimized, the dispersibility and catalytic activity of Ir nanoparticles are improved, and the mesoporous structure and surface oxygen vacancy distribution are improved, thereby greatly improving the efficiency of photocatalytic seawater hydrogen production.

[0043] When the crystal of the present invention is used to photocatalyze seawater to produce hydrogen, the reaction liquid is stirred to force convection of the reaction liquid. The specific stirring method is mechanical stirring. The crystal of the present invention has a mesoporous structure and a large specific surface area. Stirring the reaction liquid can help water molecules quickly enter the mesoporous structure and react with more active sites, thereby improving the catalytic efficiency; in addition, stirring helps to disperse the Cl2 or ClO that may be generated. - By-products such as chlorine and chlorine can be removed to reduce the corrosion of crystals and extend the life of the catalyst.

[0044] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A nano-mesoporous Ir / TiO2 crystal, characterized in that: The crystal is composed of nano-scale Ir metal particles uniformly loaded on the surface of TiO2, wherein the size of the Ir metal particles is 1-3nm, the surface of the crystal has a mesoporous structure, and the exposed crystal plane is a (101) crystal plane.

2. The nano-mesoporous Ir / TiO2 crystal according to claim 1, characterized in that: The crystal specific surface area is greater than 90m 2 / g.

3. A method for preparing nano-mesoporous Ir / TiO2 crystals, characterized in that: The following steps are involved: Step 1: Dissolve Ti(C4H9O)4 and IrCl4·xH2O in ethylene glycol, add KOH solution, stir evenly and transfer to a stainless steel reactor. After constant temperature reaction, freeze centrifuge the product, wash it repeatedly, and dry it in a vacuum drying oven to obtain the precursor Ir / K2Ti8O 17 ; Step 2: Precursor Ir / K2Ti8O 17 Mix with HCOOH, after etching reaction, take the suspension, freeze centrifuge to obtain precipitation, wash repeatedly, and place the product in a vacuum drying oven to obtain nano-mesoporous Ir / TiO2 crystals.

4. The method for preparing nano-mesoporous Ir / TiO2 crystals according to claim 3, characterized in that: In step 1, the temperature in the reactor is controlled at 200° C. for 20 hours.

5. The method for preparing nano-mesoporous Ir / TiO2 crystals according to claim 4, characterized in that: In step 2, the etching reaction is carried out in a closed stainless steel reactor.

6. The method for preparing nano-mesoporous Ir / TiO2 crystals according to claim 5, characterized in that: In step 2, the etching reaction time is 2 hours.

7. The method for preparing nano-mesoporous Ir / TiO2 crystals according to claim 6, characterized in that: In step 2, the centrifugation operation was performed under refrigerated conditions at 4°C and a rotation speed of 8000 rpm.

8. The method for preparing nano-mesoporous Ir / TiO2 crystals according to claim 7, characterized in that: In step 2, the temperature of the vacuum drying oven is 70°C.

9. Application of nano-mesoporous Ir / TiO2 crystals in photocatalytic hydrogen production from seawater, characterized in that: The crystals are catalysts.

10. The use of nano-mesoporous Ir / TiO2 crystals in photocatalytic hydrogen production from seawater as claimed in claim 9, characterized in that: The photocatalytic performance of the crystal in a simulated seawater environment with a salt content of 3.5% is better than that in a pure water environment.

Citation Information

Cited By

  • Iridium catalyst and preparation and application thereof

    CN121295232A